Stress, Cortisol and NR3C1 in At-Risk Individuals for Psychosis: A Mendelian Randomization Study - Iftimovici, Anton; Kebir, Oussama; He, Qin; Jay, Thérèse M.; , ICAAR Study Group; Rouleau, Guy A.; Krebs, Marie-Odile; Chaumette, Boris; Amado, Isabelle; Bourgin, Julie; Huard, Claire Daban; Mam-Lam-Fook, Célia Jantac; et al. (Frontiers in Psychiatry, 2020)
Introduction: The emergence of psychosis in at-risk individuals results from interactions between genetic vulnerability and environmental factors, possibly involving dysregulation of the hypothalamic-pituitary-adrenal axis. Hypercorticism was indeed described in schizophrenia and ultra-high-risk states, but its association with clinical outcome has yet to be demonstrated. The impact of stress through cortisol may vary depending on the expression level of genes related to the stress pathway. Methods: To test this hypothesis, we selected NR3C1, the gene encoding the glucocorticoid receptor, and modeled through logistic regression how its peripheral expression could explain some of the risk of psychosis, independently of peripheral cortisol levels, in a French longitudinal prospective cohort of 133 at-risk individuals, adjusted for sex, age, cannabis and antipsychotic medication intake. We then performed a genome-wide association analysis, stratified by sex (55 females and 78 males), to identify NR3C1 expression quantitative trait loci to be used as instrumental variables in a Mendelian randomization framework. Results: NR3C1 expression was significantly associated with a higher risk of conversion to psychosis (OR = 2.03, p = 0.03), independently of any other factor. Cortisol was not associated with outcome nor correlated with NR3C1. In the female subgroup, rs6849528 was associated both with NR3C1 mRNA levels (p = 0.015, Effect-Size = 2.7) and conversion (OR = 8.24, p = 0.03). Conclusions: For the same level of cortisol, NR3C1 expression increases psychotic risk, independently of sex, age, cannabis, and antipsychotic intake. In females, Mendelian randomization confirmed NR3C1’s effect on outcome to be unbiased by any environmental confounder.